Effects of Demographic Factors on Performance Strategies and Brain Wave Quality on Performance among Athletes - Mazlina Ghazali, Nor; Fauzan, Norsiah; Anuar, Azzahrah; Aden, Edris; Marzuki Wan Jaafar, Wan (International Journal of Engineering and Technology, 2018)
The purpose of this research is to investigate the effects of demographic factors and brain wave quality on performance strategies among athletes. The demographic factors such as gender, years of study, and years of involvement in sports play an important role in the use of performance strategies in determining their performance strategies in sports. The instruments used for this research is the Test of Performance Strategies (TOPS) to measure the performance strategies. The findings have revealed that there were significant differences in the performance strategies by the demographic factors as follows; gender at t (21) = 13.75; p < .05; years of study at t (21) = 9.46;Â Â p < .05, and years of involvement at t (20) = 11.37; p < .05. In addition, there were also significant differences in the sub factors of the performance strategies such as goal setting, relaxation, activation, imagery, self-talk, attentional control, emotional control, and automaticity. Based on the finding from the qEEG application, in the stroop effect tasks, the Beta and Gamma wave had the tendency to dominate the Frontal region (Fp1,Fp2), somatosensory area (C3,C4) which related to the development of the psychomotor skills and visual spatial area (P3,P4) and O1 and O2. The athletes have less thought process in seconds prior to the shot and have quieter mind than the non-athletes. It could be inferred that the athletes needed to be calm and relaxed while facing their challenge so that they could focus on their target and performance. The implication of this research includes the brain wave quality and effect on the performance strategies. The improvement in the brain quality (Alpha, Beta and Gamma) wave would assist the athletes to perform.Â Â